Line 8: Line 8:
 
Union is distributive over intersection ,i.e. <br/>
 
Union is distributive over intersection ,i.e. <br/>
 
<math>A\cup (B\cap C) = (A\cup B)\cap (A\cup C)</math> <br/>
 
<math>A\cup (B\cap C) = (A\cup B)\cap (A\cup C)</math> <br/>
where <math>A</math>, <math>B</math> and <math>C</math> are events in a probability space.
+
where <math>A</math>, <math>B</math> and <math>C</math> are sets.
  
  
Line 16: Line 16:
  
 
Let x ∈ A ∪ (B ∩ C). Then, x ∈ A or x ∈ (B ∩ C), or both. <br/>
 
Let x ∈ A ∪ (B ∩ C). Then, x ∈ A or x ∈ (B ∩ C), or both. <br/>
If x ∈ A, then x ∈ (A ∪ B), since A ⊂ (A ∪ B). <br/>
+
If x ∈ A, then x ∈ (A ∪ B), since A ⊂ (A ∪ B) ([[Union_and_intersection_subsets_mh|proof]]). <br/>
 
Similarly, we can argue that x ∈ A ⇒ x ∈ (A ∪ C), since A ⊂ (A ∪ C).
 
Similarly, we can argue that x ∈ A ⇒ x ∈ (A ∪ C), since A ⊂ (A ∪ C).
 
Therefore, x ∈ A ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C).<br/>
 
Therefore, x ∈ A ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C).<br/>
If, instead, x ∈ (B ∩ C), then x ∈ B ⇒ x ∈ (A ∪ B), since B ⊂ (A ∪ B). <br/>
+
If, instead, x ∈ (B ∩ C), then x ∈ B ⇒ x ∈ (A ∪ B), since B ⊂ (A ∪ B) ([[Union_and_intersection_subsets_mh|proof]]). <br/>
 
x ∈ (B ∩ C) also implies that x ∈ C ⇒ x ∈ (A ∪ C), since C ⊂ (A ∪ C). <br/>
 
x ∈ (B ∩ C) also implies that x ∈ C ⇒ x ∈ (A ∪ C), since C ⊂ (A ∪ C). <br/>
 
Therefore, x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C). <br/>
 
Therefore, x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C). <br/>
Line 25: Line 25:
  
 
Next, assume that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ (x ∈ A or x ∈ B) and (x ∈ A or x ∈ C) ⇒ x ∈ A or (x ∈ B and x ∈ C) ⇒ x ∈ A or x ∈ (B ∩ C) ⇒ x ∈ A ∪ (B ∩ C). <br/>
 
Next, assume that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ (x ∈ A or x ∈ B) and (x ∈ A or x ∈ C) ⇒ x ∈ A or (x ∈ B and x ∈ C) ⇒ x ∈ A or x ∈ (B ∩ C) ⇒ x ∈ A ∪ (B ∩ C). <br/>
And we have that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ A ∪ (B ∩ C), i.e. (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C)
+
And we have that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ A ∪ (B ∩ C), i.e. (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C).
  
 
Since A ∪ (B ∩ C) ⊂ (A ∪ B) ∩ (A ∪ C) and (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C), we have that A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ C).<br/>
 
Since A ∪ (B ∩ C) ⊂ (A ∪ B) ∩ (A ∪ C) and (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C), we have that A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ C).<br/>

Latest revision as of 11:24, 1 October 2013


Theorem

Union is distributive over intersection ,i.e.
$ A\cup (B\cap C) = (A\cup B)\cap (A\cup C) $
where $ A $, $ B $ and $ C $ are sets.



Proof

Let x ∈ A ∪ (B ∩ C). Then, x ∈ A or x ∈ (B ∩ C), or both.
If x ∈ A, then x ∈ (A ∪ B), since A ⊂ (A ∪ B) (proof).
Similarly, we can argue that x ∈ A ⇒ x ∈ (A ∪ C), since A ⊂ (A ∪ C). Therefore, x ∈ A ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C).
If, instead, x ∈ (B ∩ C), then x ∈ B ⇒ x ∈ (A ∪ B), since B ⊂ (A ∪ B) (proof).
x ∈ (B ∩ C) also implies that x ∈ C ⇒ x ∈ (A ∪ C), since C ⊂ (A ∪ C).
Therefore, x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C).
So we have that x ∈ A ∪ (B ∩ C) ⇒ x ∈ (A ∪ B) ∩ (A ∪ C), or equivalently, that A ∪ (B ∩ C) ⊂ (A ∪ B) ∩ (A ∪ C).

Next, assume that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ (A ∪ B) and x ∈ (A ∪ C) ⇒ (x ∈ A or x ∈ B) and (x ∈ A or x ∈ C) ⇒ x ∈ A or (x ∈ B and x ∈ C) ⇒ x ∈ A or x ∈ (B ∩ C) ⇒ x ∈ A ∪ (B ∩ C).
And we have that x ∈ (A ∪ B) ∩ (A ∪ C) ⇒ x ∈ A ∪ (B ∩ C), i.e. (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C).

Since A ∪ (B ∩ C) ⊂ (A ∪ B) ∩ (A ∪ C) and (A ∪ B) ∩ (A ∪ C) ⊂ A ∪ (B ∩ C), we have that A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ C).
$ \blacksquare $



Back to list of all proofs

Alumni Liaison

ECE462 Survivor

Seraj Dosenbach